2014
DOI: 10.1186/s13570-014-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral livelihoods of the Fulani on the Jos Plateau of Nigeria

Abstract: The Jos Plateau is an important cattle-producing area in Nigeria, with a high concentration of pastoral Fulani. In recent decades, pastoralist studies have focused on arid and semi-arid areas, with few based in the sub-humid zones, such as the Jos Plateau. There have been significant socio-economic and agricultural changes in this area over time which makes it necessary to assess current pastoral livelihood strategies. A pastoral livelihood analysis of 66 individual households/herds across 30 villages was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 18 publications
5
38
2
2
Order By: Relevance
“…The sex ratio is comparable to that on the Jos Plateau (Majekodunmi et al 2014) and that reported by van Raay (1975). The number of male cattle was observed to decline as animals reached maturity, with females over two years old making up more than half of the herd.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The sex ratio is comparable to that on the Jos Plateau (Majekodunmi et al 2014) and that reported by van Raay (1975). The number of male cattle was observed to decline as animals reached maturity, with females over two years old making up more than half of the herd.…”
Section: Discussionsupporting
confidence: 89%
“…The average calf mortality rate in KGR was 13.3%, similar to that observed in the Jos Plateau (Majekodunmi et al 2014) and figures of 10 to 15% recorded by Demiruren (1974) and Williamson and Payne (1965). The calf mortality rate was significantly higher than that observed in adults indicating that disease and/or under-nutrition in the first year of life impacts on herd productivity.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Depending solely on livestock for meat, milk and cash meant that pastoralists are prone to income fluctuations resulting from cattle devaluation, diseases, scarcity of quality feed and conflict (Majekodunmi et al 2014). Opportunities for alternative and supplementary livelihoods were limited in all the surveyed villages.…”
Section: Discussion Unpacking the Implications Of The Cwcvi-dei Assesmentioning
confidence: 99%